Blood-brain barrier in health and disease - Davis, Thomas (Henry Stewart Talks, 2008)
The blood-brain barrier is not a static barrier, The blood-brain barrier does inhibit drug delivery to the brain, The blood-brain barrier is at the level of the endothelial cell cytoarchitecture that line all cerebral blood vessels in the brain, The blood-brain barrier consists of a unique set of regulated proteins held together in a tight cytoarchitectural matrix to form a tight junction, Stressors such as head injury, hypoxia, pain and diseases such as M.S, diabetes, Alzheimer's, cancer and stroke alter tight junction proteins of the blood-brain barrier leading to a "leak" and a loss of integrity, Understanding what controls the integrity of the blood-brain barrier is critical if we are to understand how to treat the diseases of the brain
Reviewed at 2017/03/27